Impact of the COVID-19 pandemic on the diagnosis of cancer in Japan: an observational study of hospital-based cancer registries data. (July 2022) - Okuyama, Ayako; Watabe, Mari; Makoshi, Riko; Takahashi, Hirokazu; Tsukada, Yoichiro; Higashi, Takahiro
Abstract: Background: There is an important concern that the COVID–19 pandemic has negatively affected cancer care worldwide. We used a national database to assess the effect of the COVID–19 pandemic on the diagnosis of cancer in Japan. Methods: We used data from hospital-based cancer registries from 735 hospitals in Japan, covering more than 70% of newly diagnosed cases in 2018, and compared it with the 2016–19 average. We examined the monthly trends of cancer registrations in 2020 by cancer, detection process, the Union for International Cancer Control staging classification, and area. Findings: Overall, the number of patients starting treatment for cancer decreased by 1·9% in 2020, compared with the 2016–19 average. The greatest decrease was observed for stomach cancer (13·8%). The most pronounced decrease happened in May, 2020 (22·0% decrease for all cancers). The number of cases detected by cancer screening in five cancers (stomach, colon and rectum, breast, and cervix cancer) decreased substantially (by 8·1–24·3%). The number of registered cases of stage I and II gastric cancer, stage II intrahepatic cholangiocarcinoma, stage II oesophageal cancer, stage 0 and I laryngeal cancer, and stage II gallbladder cancer in 2020 decreased by more than 10% compared with the previous 2 years (2018–19). The decrease in May, 2020, was slightly greater in 13 prefectures where special precautions to prevent the spread of SARS-CoV-2 were required than in other areas not subjected to the same measures. Interpretation: The COVID–19 pandemic has led to a reduction in the number of patients diagnosed with cancer and starting treatment in Japan, particularly when the Japanese Government declared a state of emergency in April, 2020. Funding: This study was supported by the Health, Labour and Welfare Policy Research Grants, Research for Promotion of Cancer Control Programmes (reference 21EA2003), and the Cancer Research and Development Fund of the National Cancer Centre, Japan (reference 2020–A–20).